Hydrodynamics of Abyssal Channel Flows - V.Yu. Liapidevskii; N.I. Makarenko; E.G. Morozov; R.Yu. Tarakanov (Учёные записки Казанского университета: Серия Физико-математические науки)
This paper presents a survey of the recent results of field observations over near-bottom stratified flows in the abyssal channels of the Atlantic Ocean, as well as the results of mathematical modeling and laboratory experiments related to generic hydrodynamic phenomena. The main attention is devoted to such characteristic features of these flows as splitting of inclined gravity currents, formation of critical layers in the shear flows over the obstacles, and fragmentation of near-field structures formed by the internal stationary waves in the vicinity of complex obstacles.